THE ROLE OF BIOTECHNOLOGY IN DENGUE VIRAL INFECTION : Effort for The Development of A Dengue Vaccine - Djoni Djunaedi (Saintika Medika, 2011)
Introduction: Dengue fever and Dengue Haemorrhagic Fever (DF/DHF) are caused by dengue viruses (DENV). There are four antigenically related but distinct DENV serotypes (DENV-1 through DENV-4). Humans are the amplifying vertebrate host and Aedes mosquitos are the primarily mosquito vector as well as the reservoir of infection. DENV infection causes a spectrum of diseases, ranging from asymptomatic infections to infections complicated by haemorrhagic shock and death (Yoksan, 2008). Epidemiology: WHO (2008) estimates that about 2.5 billion people or 40% of the world’s population live in areas where there is a risk of dengue transmission. About 500,000 cases of dengue’s severest form (DHF/DSS) occur annually, resulting in about 24,000 deaths, mostly among children. Tropical and subtropical areas of South East Asia and Latin America are the hardest hit by dengue infection. Although dengue rarely occurs in the continental United States, it is endemic in Puerto Rico and Hawaii, a U.S. territory. Mosquitos capable of transmitting the virus have been found in the U.S. (in Florida, Georgia, Louisiana, Alabama, Mississippi, and Texas) over the last 10 years (Cano and Bannister, 2001; CDC, 2009; Science News, 2010). Facing this problem, vaccination is the answer. Vaccine Development: Dengue is an expanding public health problem, and an effective vaccine remains elusive. Significant influence of sequential infections with different dengue virus serotypes on the severity of disease can be viewed in terms of beneficial and detrimental effects of the heterologous immunity. A more complete understanding of these effects is likely to be critical for predicting optimal vaccine – induced immune responses, with the aim of protecting the global population from emerging infectious disease threats (Rothman, 2004). In 1980, Mahidol University committed to develop a live-attenuated tetravalent DENV vaccine. They were subjected to general safety test and monkey neurovirulence tests in accordance with the U.S. FDA requirements. (Yoksan 2008) Results: All vaccine recipients developed either a mild or no adverse reaction to the vaccine, the immunogenicity data were discussed. The current strategy of creating tetravalent DENV vaccine formulation can lead to an unbalanced immune response. This is attributed to viral interference that apparently comes into play when three monovirulent vaccine viruses DENV-1, DENV-2, DENV-4 are mixed with DENV-3 to create a tetravalent formulation (Yoksan, 2008). Summary: More research is needed on a priority basis to work out the viral interference factor in order to make the production of a tetravalent vaccine out of the attenuated DENV-3 candidate vaccine strain a success. Key words: Dengue Haemorrhagic Fever, Shock and death, tetravalent dengue vaccine, viral interference factor.